(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Coal based thermal power plants generates huge amount of fly ash as waste worldwide. This coal fly ash was modified by alkaline hydrothermal treatment and termed as modified coal fly ash (MCFA), which was then used as an adsorbent for phenol removal from aqueous solution using packed bed adsorption column. The effect of bed height (7.5, 13.5, 27.5 cm), flow rate (0.375, 0.75, 1.0 ml/min) and initial phenol concentration (70.0, 292.7, 651.2, 1039.9 mg/l) on the breakthrough curve and adsorption performance was investigated. The various process parameters such as breakthrough capacity (qb), volume of effluent treated (Veff), mass transfer zone (MTZ) and fractional bed utilization (FBU) were investigated to evaluate the column performance. The results showed that for the flow rate of 1.00 ml/min, initial phenol concentration of 1039.9 mg/l and bed height of 13.5 cm, the maximum column capacity (at 80% breakthrough) was obtained to be 67.724, 17.472 and 62.150 mg/g during the column study for effect of different bed height, flow rate and phenol concentration respectively. It was observed that, the column performance was affected by flow rate, bed height and initial phenol concentration.